Pediatric Palatal Fibroma - Mishra, Rahul (Int J Clin Pediatr Dent, 2017)
Fibroma is one of the most common soft tissue benign tumors of the oral cavity. These masses represent hyperplasias instead of true neoplasm, which develop due to irritation to the mucosal tissue resulting in proliferation of the cells. Although so common in the oral cavity, its occurrence on the palate is rare, mainly due to fewer chances of trauma. Here, we report a case of palatal fibroma in a child diagnosed on the basis of clinical, radiological, and histological features. The case represents an extremely rare occurrence as unusual trauma due to thumb sucking seemed to be the only apparent traumatic factor in the palatal region. HOW TO CITE THIS ARTICLE: Mishra R, Khan TS, Ajaz T, Agarwal M. Pediatric Palatal Fibroma. Int J Clin Pediatr Dent 2017; 10(1):96-98.